2003
DOI: 10.1007/s00421-002-0719-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in isometric contraction properties of rat diaphragm during hypoxia

Abstract: Hypoxia disturbs Ca(2+) regulation and increases the intracellular Ca(2+) concentration ([Ca(2+)](i)), which may in turn activate the nitric oxide synthase (NOS) regulated by [Ca(2+)](i). Since nitric oxide (NO) reduces the isometric contractility of rat diaphragm in vitro, we hypothesized that NO contributes to the impaired force generation of an hypoxic diaphragm. The effects of different concentrations of the NOS inhibitor, N(G)-monomethyl-L-arginine (L-NMMA), the NO scavenger haemoglobin (150 micro mol.l(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
4
13
0
Order By: Relevance
“…It is also unlikely that the duration of exposure to hypoxia plays a role as a decline in force was already detected after 2 min of hypoxia, 6 whereas others found no change in MVC even after a 40-day simulated climb. 10 Whereas in vivo force-generating capacity of the muscle tissue itself seems to be maintained during hypoxia, in vitro studies generally show a decline in force-generating capacity 2,17,20,26 and a downward shift of the force-frequency relation. 18 We did not find such a depression of force or shift in the forcefrequency relation in the in vivo situation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It is also unlikely that the duration of exposure to hypoxia plays a role as a decline in force was already detected after 2 min of hypoxia, 6 whereas others found no change in MVC even after a 40-day simulated climb. 10 Whereas in vivo force-generating capacity of the muscle tissue itself seems to be maintained during hypoxia, in vitro studies generally show a decline in force-generating capacity 2,17,20,26 and a downward shift of the force-frequency relation. 18 We did not find such a depression of force or shift in the forcefrequency relation in the in vivo situation.…”
Section: Discussionmentioning
confidence: 96%
“…20 Indeed, hemoglobin, a scavenger of nitric oxide (NO), in the incubation medium alleviated the effects of an NO donor on in vitro diaphragm contractility during hypoxia. 26 As myoglobin not only plays a role in O 2 storage and facilitated diffusion but also as an intracellular scavenger of NO and reactive oxygen species (ROS), 19 it is possible that in vivo the hemoglobin in the blood and the intracellular myoglobin scavenge the NO and ROS to such an extent that during acute hypoxia for a limited period their detrimental effect on in vivo skeletal muscle function is attenuated. Indeed, it has been reported that acute hypoxemia does not induce oxidative stress in muscle in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility is a mechanism similar to that described by Maréchal & Beckers-Bleukx (1998) and Zhu et al (2003), associated with the production of NO.…”
Section: Changes In V Max and Powermentioning
confidence: 99%